2011
DOI: 10.1364/oe.19.021855
|View full text |Cite
|
Sign up to set email alerts
|

Spectral encoding of x-ray/optical relative delay

Abstract: We present a new technique for measuring the relative delay between a soft x-ray FEL pulse and an optical laser that indicates a sub 25 fs RMS measurement error. An ultra-short x-ray pulse photo-ionizes a semiconductor (Si(3)N(4)) membrane and changes the optical transmission. An optical continuum pulse with a temporally chirped bandwidth spanning 630 nm-710 nm interacts with the membrane such that the timing of the x-ray pulse can be determined from the onset of the spectral modulation of the transmitted opti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
118
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 131 publications
(119 citation statements)
references
References 19 publications
0
118
0
1
Order By: Relevance
“…However, RF based sources still suffer from a major complication: the synchronization between the laser oscillator and RF electronics. State of the art free electron laser facilities such as the Linac Coherent Light Source (LCLS) still report nominal timing jitter between laser and X-ray of 100-200 fs RMS, 14 and RF compressed electron sources have reported similar quantities. 12,13 However, work at LCLS has recently demonstrated that timing jitter can be mitigated by several single shot time stamping techniques.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, RF based sources still suffer from a major complication: the synchronization between the laser oscillator and RF electronics. State of the art free electron laser facilities such as the Linac Coherent Light Source (LCLS) still report nominal timing jitter between laser and X-ray of 100-200 fs RMS, 14 and RF compressed electron sources have reported similar quantities. 12,13 However, work at LCLS has recently demonstrated that timing jitter can be mitigated by several single shot time stamping techniques.…”
mentioning
confidence: 99%
“…12,13 However, work at LCLS has recently demonstrated that timing jitter can be mitigated by several single shot time stamping techniques. [14][15][16][17][18] With electrons, electro-optic sampling techniques can be used in a similar fashion for bunch charges more than a few pC. 19 For the typical fC bunches used in UED (Ultrafast Electron Diffraction), no current technique is sensitive enough to determine the arrival time of individual pulses with respect to the excitation laser.…”
mentioning
confidence: 99%
“…In this low-charge operation mode, an external pulse such as an optical laser can be adopted as a pump. However, the synchronization jitter between the pump and probe pulses is very challenging and many efforts have been made to solve this problem (see, e.g., [4], [5], and references therein).…”
mentioning
confidence: 99%
“…In recent years various methods have been proposed and developed for accurate measurements of relative arrival times (Bionta et al, 2011;Tavella et al, 2011;Dü sterer et al, 2011; Ding et al, 2011;Dü sterer et al, 2011;Inubushi et al, 2012;Grguraš et al, 2012;Riedel et al, 2013). Among these methods, the THz streak camera (Itatani et al, 2002;Frü hling et al, 2009;Grguraš et al, 2012;Helml et al, 2014;Juranić et al, 2014b) is able to measure both the length and the arrival time of the photon pulses at wavelengths ranging from UV to hard X-ray.…”
Section: Introductionmentioning
confidence: 99%